THE EFFECT OF WORK COMMUNICATION, MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE PT. SEVEN SURABAYA JAYA IN SIDOARJO - Dina Ramawati; Hermien Tridayanti (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2020)
This study aims to determine the effect of communication variables, motivation and work discipline, on employee performance variables of PT. Seven Surabaya Jaya in Sidoarjo, partially or simultaneously. The method used is quantitative and data obtained from this study from the distribution of questionnaires given to 52 employees, which are then analyzed using multiple linear regression analysis that is processed with SPSS version 26. The results of the F test indicate that the variables of communication, motivation and discipline work has a significant effect on employee performance jointly or simultaneously. While the results of the t test show that the variables of communication, motivation and work discipline affect the performance of employees individually or partially. From the results of this study it is recommended that companies pay more attention to communication between employees, pay more attention to providing motivation to employees and remind employees about the regulations in the company.